Feeling safe while doing sex work: Motivation for entering sex work moderates the relationship between perceptions of physical danger and desire to leave sex work. (September 2020) - Arnold, Kara A.; Turner, Nick; Barling, Julian; Iverson, Roderick D.
Highlights: Perceived physical danger linked with desire to leave when extrinsically motivated. If entered for intrinsic reason may not be as deterred by physical danger perception. Sex Industry Survey (Pyett et al., 1994) a rare sample. Safety-related research of an under-researched and vulnerable population of workers. Abstract: Large segments of society stigmatize sex work as 'dirty' because of the moral dubiousness and physical danger associated with its conduct. Drawing on social exchange and self-determination theories, we investigated the relationship between perceptions of physical danger at work and desire to leave sex work as an occupation among 321 female sex workers in Melbourne, Australia. We examined reasons for entering the occupation of sex work as a moderator of this relationship. Under conditions of high perceptions of physical danger, women who cited extrinsic (largely economic) reasons for choosing sex work reported higher desire to leave sex work than women who cited intrinsic (personal) reasons for choosing sex work did. Levels of desire to leave sex work of women who reported intrinsic reasons for choosing sex work did not differ across levels of perceived physical danger. As such, we consider the 'dark side' of intrinsic reasons for choosing work that may inadvertently deter respondents from wanting to leave physically dangerous work.